2006
DOI: 10.1007/s11069-005-4658-8
|View full text |Cite
|
Sign up to set email alerts
|

A Climatology Model for Forecasting Typhoon Rainfall in Taiwan

Abstract: The continuous torrential rain associated with a typhoon often caused flood, landslide or debris flow, leading to serious damages to Taiwan. Thus, a usable scheme to forecast rainfall amount during a typhoon period is highly desired. An analysis using hourly rainfall amounts taken at 371 stations during 1989-2001 showed that the topographical lifting of typhoon circulation played an important role in producing heavier rainfall. A climatology model for typhoon rainfall, which considered the topographical liftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 14 publications
2
61
0
1
Order By: Relevance
“…3. The strategy used to construct the rainfall climatology here is based on Lee et al (2006) and different from that in Marks et al (2002) that developed the R-CLIPER for Atlantic TCs. The latest version of R-CLIPER utilizes rain estimates from the Tropical Rain Measurement Mission (TRMM) Microwave Imager (TMI) and derives storm-centered mean rain rate distribution stratified for different TC intensities.…”
Section: Setup Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…3. The strategy used to construct the rainfall climatology here is based on Lee et al (2006) and different from that in Marks et al (2002) that developed the R-CLIPER for Atlantic TCs. The latest version of R-CLIPER utilizes rain estimates from the Tropical Rain Measurement Mission (TRMM) Microwave Imager (TMI) and derives storm-centered mean rain rate distribution stratified for different TC intensities.…”
Section: Setup Of the Modelmentioning
confidence: 99%
“…However, when a typhoon is approaching the Taiwan Island, its structure and convection distribution will be greatly affected by Taiwan's topography and highly asymmetric rainfall distribution will likely occur. For example, Lee et al (2006) showed that the features of TC rainfall in the Taiwan area are closely locked by the topography. Therefore in developing the rainfall CLIPER model for the Taiwan area, the actual climatological rainfall map is used.…”
Section: Setup Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…QPESUMS forecasts future rainfall patterns by predicting the movement paths of cloud cells. Data are provided for a wide range of applications, including typhoon rainfall forecasts (Lee et al, 2006), river flooding forecasts (Vieux et al, 2003), and landslide forecasts (Chen et al, 2007).…”
Section: Study Areamentioning
confidence: 99%
“…Most typhoons in Taiwan form between May and November, and, on average, 3.9 typhoons affect Taiwan each year. As soon as a typhoon strikes, it often causes continuous torrential rainfall, leading to severe flooding, landslides, and debris flow [1]. Therefore, an effective and quantitative precipitation forecast model for typhoon periods is necessary.…”
Section: Introductionmentioning
confidence: 99%